Determination of the interfacial electronic structure and morphology of organic semiconductor materials - Schroeder, Paul G., author; Parkinson, Bruce, advisor; Bernstein, Elliot, committee member; Levinger, Nancy, committee member; Van Order, Alan, committee member; Lee, Siu Au, committee member (Colorado State University. Libraries, 2002)
Thin films of 𝘱-quaterphenyl, 𝘱-sexiphenyl, coronene, and pentacene were each deposited sequentially in multiple steps onto different substrates including highly oriented pyrolytic graphite (HOPG), SnS2, and A u (lll). The energy level offsets at the interfaces between each organic semiconductor film and the respective substrate were subsequently measured using a combination of X-ray and ultraviolet photoelectron spectroscopy (XPS, UPS) in sim after each growth step. The organic materials used have significantly delocalized molecular orbitals, and were chosen for their potential applications in organic semiconductor devices and that they allowed for more thorough analysis of the interface. HOPG and SnS2 are layered materials that have nearly atomically flat van der Waals surfaces that could be cleaved in vacuum allowing for fundamental investigations of interfacial dipoles and the existence of band bending effects at the interfaces of organic materials. The gold substrate allowed for more applied studies into the contact interfaces used for organic thin film transistors.

The combined methods of UPS and XPS were used to more precisely determine the orbital offsets at the organic interfaces by separating out band bending, or final state screening related shifts, from the total work function measured with UPS. In addition, a method using low intensity XPS work function measurements was successfully developed to separate out sample charging artifacts from the true shifts.

Several of these systems, particularly those consisting of pentacene, were also characterized for the surface adsorption and film morphology using scanning tunneling microscopy (STM), atomic force microscopy (AFM), and temperature programmed desorption (TPD). The STM images revealed ordering of pentacene in several distinct unit cells with respect to the Au (lll) surface. Different growth patterns of pentacene deposited on Au(lll) and SnS2 were observed based on the analysis of the ultra-violet photoelectron spectra and AFM.
Keywords: chemistry; analytical chemistry; physical chemistry